Simulated Annealing (IntechOpen, 2012)
Simulated Annealing is a probabilistic meta-heuristic that is based on statistical mechanics: while at high temperatures molecules in a liquid move freely, the slow reduction of temperature decreases the thermal mobility of the molecules. The final state forms a pure crystal which also corresponds to a state of minimum energy. We encourage readers to explore SA in their work, mainly because it is simple and because it can yield very good results.